Low Power to the People. - Jones, W.D.
This paper discusses the latest battleground of low-watt community radio in Greenville, South Carolina. WMXP is the first community radio station in the said city. The Greenville radio station is a new beachhead in a conflict over whether political, ethnic, and religious groups, as well as neighborhoods and school authorities, may operate low-power FM (LPFM) radio stations, which - by dint of their small broadcast ranges - are necessarily focused on local interests.
Keywords: Greenville; South Carolina; WMXP radio station; Low-power FM radio; Low-watt community radio